Illusions of terrorism and counter-terrorism - English, Richard, 1963- (Proceedings of the British Academy ;, 2016)
aThe relationship between non-state terrorism and state counter-terrorism continues to shape world politics. Leading scholars analyse this relationship, examining post-9/11 counter-terrorism, the evolution of al-Qaida, challenges to Western counter-terrorism, and why terrorist campaigns sometimes endure and sometimes end.